2021
DOI: 10.3389/fcimb.2020.596166
|View full text |Cite
|
Sign up to set email alerts
|

Viral Infections, the Microbiome, and Probiotics

Abstract: Viral infections continue to cause considerable morbidity and mortality around the world. Recent rises in these infections are likely due to complex and multifactorial external drivers, including climate change, the increased mobility of people and goods and rapid demographic change to name but a few. In parallel with these external factors, we are gaining a better understanding of the internal factors associated with viral immunity. Increasingly the gastrointestinal (GI) microbiome has been shown to be a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
81
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 232 publications
(292 reference statements)
0
81
0
3
Order By: Relevance
“…Preventive and therapeutic vaccines have promising applications to prevent infection and treat cancer and other health issues globally (Harper et al, 2020 ). Although several vaccines against human papillomavirus (HPV), viral hepatitis, influenza, measles, varicella, rubella, mumps and rotavirus (Knuf et al, 2008 ) have been widely used to save millions of lives, vaccines for newly discovered pathogens like the respiratory virus COVID 19 are urgently needed (Du et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Preventive and therapeutic vaccines have promising applications to prevent infection and treat cancer and other health issues globally (Harper et al, 2020 ). Although several vaccines against human papillomavirus (HPV), viral hepatitis, influenza, measles, varicella, rubella, mumps and rotavirus (Knuf et al, 2008 ) have been widely used to save millions of lives, vaccines for newly discovered pathogens like the respiratory virus COVID 19 are urgently needed (Du et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal bacteria can potentially achieve distal effects on lung homeostasis through training of immune cells in the gut epithelium and their subsequent migration to the pulmonary epithelium, and/or through the permeation into the bloodstream of bacterial metabolites having distal immunomodulatory effects. 5,6…”
Section: Introductionmentioning
confidence: 99%
“…In this context, conflicting reports showed the ineffectiveness of carbohydrate supplementation to minimize URTI risk . While animal models have shown that a carbohydraterich diet reduces the risk of herpes simplex virus 1 [HSV-1] infection and mortality (Harper et al, 2021), it has also been shown that carbohydrate intake after exercise debilitates human T cells' declining migration towards human rhinovirus-infected airway epithelial cells, as seen in vitro (Peake et al, 2017). Therefore, more research regarding the effectiveness of carbohydrate supplementation with clinical relevance in a case like URTI is required.…”
Section: Carbohydratementioning
confidence: 99%
“…• Minimized exercise-induced increased circulating cytokines, redistribution of immune cells like neutrophils, monocytes, NK cells and lymphocytes (Nieman and Wentz, 2019). • Upper respiratory tract infections (URTI) recovery (Nieman and Mitmesser, 2017); reduction in risk of infection and mortality from viral infections like herpes simplex virus 1 [HSV-1] (Harper et al, 2021). Micronutrients including (antioxidant vitamins-vitamins C and E); vitamin D and multivitamin…”
Section: Carbohydrate Interventionmentioning
confidence: 99%